Post-Euromaidan Ukraine : Domestic Power Struggles and War of National Survival in 2014-2022. - Harasymiw, Bohdan (Soviet and post-Soviet politics and society., 2023)
Ukraine is a misfit among post-communist states, being neither a respectable, stable democracy nor an autocracy. Nor does it sit well as a patronal political system, like other post-Soviet regimes, since the Euromaidan Revolution. This study examines the presidencies of Petro Poroshenko and Volodymyr Zelenskyy focusing on their common tendency to subordinate the legal system and use it as a political instrument. It finds that this pattern of power struggle concentrated in the president's office was, contrary to the theory of patronal politics, more dominant than clientelism. The second theme of this book is each president's handling of relations--largely meaning the war--with Russia, in the wake of the annexation of Crimea in 2014 and culminating in the invasion of 2022, as the key challenge to the nation's survival. One way or another, unable to reform itself or to withstand the Russian assault, post-Euromaidan Ukraine will have come to an end.